Characterizing familial corticobasal syndrome due to Alzheimer's disease pathology and PSEN1 mutations. Issue 5 (13th October 2016) - Lam, Benjamin; Khan, Aun; Keith, Julia; Rogaeva, Ekaterina; Bilbao, Juan; St. George‐Hyslop, Peter; Ghani, Mahdi; Freedman, Morris; Stuss, Donald T.; Chow, Tiffany; Black, Sandra E.; Masellis, Mario
Abstract: Introduction: Corticobasal syndrome (CBS) resulting from genetic Alzheimer's disease (AD) has been described only once. Whether familial CBS‐AD is a distinct clinical entity with its own imaging signature remains unknown. Methods: Four individuals with CBS from two families underwent detailed assessment. For two individuals, regional atrophy and hypoperfusion were compared to autopsy‐confirmed typical late‐onset AD and corticobasal degeneration, as well as genetically proven PSEN1 cases with an amnestic presentation. Results: One family harbored a novel mutation in PSEN1 :p.Phe283Leu. MRI demonstrated severe parietal, perirolandic, and temporal atrophy, with relative sparing of frontal and ipsilateral hippocampal regions. Autopsy confirmed pure AD pathology. The other family harbored a known PSEN1 mutation:p.Gly378Val. Discussion: This report confirms familial CBS‐AD as a distinct clinical entity, with a parietal‐perirolandic‐temporal atrophy signature. It illustrates the clinical heterogeneity that can occur despite a shared genetic cause and underscores the need for biomarkers such as amyloid imaging during life. Highlights: CBS can result from autosomal dominant AD (familial CBS‐AD), due to PSEN1 mutations Familial CBS‐AD demonstrates a parietal‐temporal‐perirolandic atrophy pattern on MRI Familial CBS‐AD can demonstrate variable phenotype even within a single family Genetic testing, especially for PSEN1, should be considered in atypical CBS